Picomolar Detection of Tau Protein Using 1D Photonic Crystal Biochips for Alzheimer's Disease Diagnosis - Alberto Sinibaldi; Francesco Chiavaioli; Agostino Occhicone; Norbert Danz; Peter Munzert; Francesco Baldini; Ambra Giannetti; Francesco Michelotti (Advanced Sensor Research)
Abstract Alzheimer's disease (AD) is a progressive neurological disorder that gradually impairs all cognitive functions. The diagnosis typically requires a combination of cognitive assessments, neuroimaging techniques, and biomarker analysis. In healthy neurons, Tau protein stabilizes microtubules, which are vital for maintaining the structure and proper functioning of nerve cells. However, elevated levels of Tau in cerebrospinal or other body fluids can be related to the progression of Alzheimer's disease. This study introduces an optical technique that employs a dual label‐free and fluorescence operation mode to detect Tau protein in both standard running buffer and cerebrospinal fluid. This innovative method enables label‐free analysis of the bio‐conjugation process on biochips used for resolved fluorescence‐based Tau detection. This work successfully demonstrates Tau protein detection in both matrixes, achieving an outstanding limit of detection of 2.4 pM in cerebrospinal fluid. Moreover, the analysis of the dose‐response curve allows to estimate the dissociation constant (KD = 18 nM) for Tau interactions, yielding values that are in excellent agreement with existing literature using other techniques. These aspects highlight the added value of this technique, providing a valuable tool for investigating Alzheimer's‐related biomarkers, as demonstrated in this study with Tau protein.